Assessment of the Required Changes of Russian Ecological Taxes - Tagaeva, Tatiana Olegovna; Baranov, Alexander Olegovich; Gilmundinov, Vadim Manavirovich (International Journal of Energy Economics and Policy, 2016)
Russia is one of the most polluting countries in the world and environmental problem is very important in this country. The forecast of atmospheric emissions was conducted according to various economic development scenarios in Russia using dynamic Dynamic Input-Output Model. The optimistic scenario is realized under hypothesis about oil prices increase and real ruble exchange rate strengthening beginning of the end of 2015, the revival of investment processes, the successful policy of import substitution, and the competent using of instruments of monetary and fiscal policy. The pessimistic scenario is implemented under assumption of negative economic tendency prolongation of the 2014. Future increase of environmental pressure will be expected in optimistic scenario. The improvement of pollution taxes mechanism as a way of government ecological policy is discussed in the article. Keywords: Input-Output Model, environmental pollution, forecast of emission, pollution taxes JEL Classifications: E62, H23, Q32, Q38, Q42, Q5